2011
DOI: 10.1128/jb.05426-11
|View full text |Cite
|
Sign up to set email alerts
|

Long-Chain N -Acyl Amino Acid Synthases Are Linked to the Putative PEP-CTERM/Exosortase Protein-Sorting System in Gram-Negative Bacteria

Abstract: Clones that encode the biosynthesis of long-chain N-acyl amino acids are frequently recovered from activitybased screens of soil metagenomic libraries. Members of a diverse set of enzymes referred to as N-acyl amino acid synthases are responsible for the production of all metagenome-derived N-acyl amino acids characterized to date. Based on the frequency at which N-acyl amino acid synthase genes have been identified from metagenomic samples, related genes are expected to be common throughout the global bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…The phosphorylated PrsR (PrsR∼P) is activated and binds to a well conserved enhancer upstream of RpoN recognizing promoter. The bound phosphorylated PrsR polymer flips over to interact with σ 54 and activates the σ 54 ‐RNA polymerase holoenzyme (Eσ 54 ) in an ATP‐dependent process leading to transcription of downstream PEP‐CTERM gene(s) (Craig et al ., ). The PEP‐CTERM proteins are secreted into the periplasm and anchored to the cytoplasmic membrane by their PEP‐CTERM motifs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylated PrsR (PrsR∼P) is activated and binds to a well conserved enhancer upstream of RpoN recognizing promoter. The bound phosphorylated PrsR polymer flips over to interact with σ 54 and activates the σ 54 ‐RNA polymerase holoenzyme (Eσ 54 ) in an ATP‐dependent process leading to transcription of downstream PEP‐CTERM gene(s) (Craig et al ., ). The PEP‐CTERM proteins are secreted into the periplasm and anchored to the cytoplasmic membrane by their PEP‐CTERM motifs.…”
Section: Discussionmentioning
confidence: 99%
“…S10). The gene products are probably acidic proteins of similar sizes (212-359 residues) and contain an abundance of residues that potentially could be used for O-linked and N-linked glycosylation at Ser/ Thr and/or Asn residue respectively (Craig et al, 2011). Asparagine (Asn or N) is overrepresented in the PepA polypeptide and 8 of the 18 N are part of the Nx[ST] motif for N-linked glycosylation in eukaryotes (Mononen and Karjalainen, 1984).…”
Section: Rpon Sigma Factor Is Required For Floc Formationmentioning
confidence: 99%
“…The domains from LuxI containing protein of Gram-positive bacteria are related to autoinducer synthesis. For example, “ Autoinducer synthase ” (IPR001690, IPR018311) responsible for synthesizing AHLs by utilizing acyl-(acyl-carrier proteins) (acyl-ACP) and amino acids as substrates in the presence of acyl transferase (IPR016181, Acetyltransf_5) 37 . Likewise, among LuxR containing proteins i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Functional annotation of potential LuxI/LuxR incorporating proteins was accomplished using GO and ligand-based analysis. As LuxI containing proteins was assigned with “ transferase activity ”, which might helps Gram-positive bacteria to transfer acyl group during AHL synthesis 37 , 40 . In case of LuxR, predominant biological processes involve in DNA dependent and gene-specific transcription.…”
Section: Discussionmentioning
confidence: 99%
“…While this work was under review, Craig et al (10) reported that a previously uncharacterized family of acyltransferases regularly found in bacteria in gene neighborhoods shared with exosortases attach long-chain acyl groups to free amino acids. Because acyltransferase activity was characterized in heterologous systems possessing neither exosortase nor its putative PEP-CTERM targets, this work leaves open the possibility that these acyltransferases are involved primarily in PEP-CTERM protein modification, rather than in the production of a bioactive small molecule, as the article suggests, or in the modification of extracellular polysaccharides.…”
Section: Discussionmentioning
confidence: 99%